Socialization of Cassava Tuber Development and Marketing as a Creative Culinary Product of Local Wisdom for the Community on Lance Island Barelang Batam City - Syaiful, Hendra (PUSLITABMAS-Politeknik Pariwisata Batamc, 2025)
Socialization of Cassava Development and Marketing. This title describes an educational activity aimed at providing the community with an understanding of how to develop the potential of cassava tubers such as cassava (singkong), sweet potato (ubi jalar), and taro (talas) into processed products with economic value. Furthermore, this activity also emphasizes the importance of marketing strategies so that tuber-based products can become more widely known and have competitiveness in the market. This socialization includes: Education on innovative processing of cassava tubers into creative culinary or non-culinary products. Marketing training, both traditionally and digitally. Community empowerment so that cassava tubers can become a source of business and local economic improvement. Overall, this title indicates that cassava tubers are not only a food source but also a strategic commodity that can encourage creativity, entrepreneurship, and local economic resilience